Work from Home and the Office Real Estate Apocalypse - Gupta, Arpit; Mittal, Vrinda; Nieuwerburgh, Stijn Van (American Economic Review, 2026)
We show remote work led to large drops in lease revenues, occupancy, and market rents in the commercial office sector. We revalue New York City office buildings, taking into account both the cash flow and discount rate implications of these shocks, and find a 46 percent decline in long-run value. For all US office markets combined, we find a $556.8 billion value destruction. Higher-quality buildings were buffered against these trends due to a flight to quality, while lower-quality offices are at risk of becoming a stranded asset. These valuation changes have repercussions for financial stability and local public finances. (JEL E31, E32, G12, J22, M51, R33)